"Validación del proceso fermentativo de una bebida a partir de zanahoria amarilla (Daucus carota) y remolacha (Beta vulgaris) - Moreno Riquero, Cristhian Andrés (2020)
In this research work, a fermented beverage was obtained from yellow carrot (Daucus carota) and beet (Beta vulgaris) by applying four clarifiers in the following percentages: carrageenan 0.1 g/L, Irish Moss 1.25 g/L, moringa 2 g/L and Cmc 1 g/L, to be evaluated by sensory analysis. In this sense, the general objective of this research was to validate the fermentative process of yellow carrot (Daucus carota) and beet (Beta vulgaris), where it was decided to supply some clarifiers such as Carrageenan, moringa, Carboxy methyl cellulose and Irish Moss, to observe which shows a better effect in the clarification stage, resulting in a product clean of turbidity. The raw material was obtained in the market of Quevedo, the same that were free of any impurity, we proceeded to wash and peel the fruit and then perform the extraction of juice, which was conditioned properly. In a period of ten to fifteen days the fermentation was carried out in which after this period of time the clarifiers were added to continue with the maturation, it was left to rest for 45 days at room temperature in a place free of light. The applied experimental design was a factorial arrangement AxB Completely Randomized Experimental Design (DCA). With the application of an analysis of variance with respect to each study variable, 8 treatments and 2 replications were determined, giving a total of 16 experimental units, obtaining as the best treatment a0b0 (Yellow Carrot + Carrageenan) a semi-sweet drink with values °Brix 6.9, pH 4.05, alcoholic degrees 10.93, total acidity (% citric acid) 0.45, ash 6.295, turbidity 1.178, density 1.082. Key words: Yellow carrot, Beet, Clarifiers, Fermentation, Maturation.